Hydrology - The Science of Water 2019
DOI: 10.5772/intechopen.82399
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Non-Rainfall Periods and Their Impacts on the Soil Water Regime

Abstract: Rainfall and evaporation belong to the basic components of the hydrological cycle. Rainfalls are a decisive natural source of water in the soil. For water replenishment in the natural environment, it is important not only the sum of the rainfall for the balanced period but also the time distribution. In the case of long non-rainfall periods, the soil profile is dried. In the sufficiently long non-rainfall period, the water reserves in the unsaturated zone of the soil profile change and the actual evapotranspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…Therefore, it is important to consider not only macrosynoptic factors but also local geographic conditions in these studies. Some scientists believe that a day without precipitation can also be considered if more than 2 mm of precipitation does not fall per day (Byun & Wilhite, 1999;Gomboš et al, 2019), or more than 3 mm of precipitation during the vegetation period (Srdjevic et al, 2022), because this amount of precipitation has almost no effect on ecosystems. When defining the number of days without precipitation necessary for the onset of drought in our latitudes, some authors believe that there should be a period of at least 15 consecutive days (Huschke, 1970), others say that such a period should be longer than 20 days (Hlásny et al, 2015;Srdjevic et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is important to consider not only macrosynoptic factors but also local geographic conditions in these studies. Some scientists believe that a day without precipitation can also be considered if more than 2 mm of precipitation does not fall per day (Byun & Wilhite, 1999;Gomboš et al, 2019), or more than 3 mm of precipitation during the vegetation period (Srdjevic et al, 2022), because this amount of precipitation has almost no effect on ecosystems. When defining the number of days without precipitation necessary for the onset of drought in our latitudes, some authors believe that there should be a period of at least 15 consecutive days (Huschke, 1970), others say that such a period should be longer than 20 days (Hlásny et al, 2015;Srdjevic et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Drying of soil profile occurs during long rainless periods. Meteorological drought and subsequently soil drought occurs in the case of the sufficiently long rainless period (Gomboš et al, 2019). Therefore it is necessary to know the size and statistical characteristics of non-precipitation periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the analyses demonstrated that, after a dry spell lasting for only 10 days, the moisture decrease varied from 7% for the layer of 20-40 cm to 19% and 35%, respectively, for the adopted for the layer of cm, while a 40-day non-rainfall period caused soil moisture to decrease by 27% for the layer of 20-40 cm and 57% and 82%, respectively, for the layer of 0-10 cm (Table According to the research of Flammini et al [79] the dynamics of evaporation in bare soil in dry summer periods, the initial moisture affects the drying process. Gomboš et al [85] indicate, on the basis of simulated soil values, that during non-rainfall periods, water retention in soil under vegetation cover largely on the value of actual evapotranspiration. The level of limitation of the process in spell conditions can be an indicator of the drying of the soil profile.…”
Section: Discussionmentioning
confidence: 99%
“…According to the research of Flammini et al [79] on the dynamics of evaporation in bare soil in dry summer periods, the initial soil moisture affects the drying process. Gomboš et al [85] indicate, on the basis of simulated soil moisture values, that during non-rainfall periods, water retention in soil under vegetation cover largely depends on the value of actual evapotranspiration. The level of limitation of the process in dry spell conditions can be an indicator of the drying of the soil profile.…”
Section: Discussionmentioning
confidence: 99%